Cysteamine-functionalized silver nanowires as hydrogen donor for type II photopolymerization - Altinkok, Cagatay; Oytun, Faruk; Basarir, Fevzihan; Tasdelen, Mehmet Atilla (Elsevier BV, 2017)
Abstract A versatile method for the in-situ preparation of poly(methyl methacrylate)/silver nanowire (PMMA/AgNW) nanocomposites has been reported. The use of cysteamine-functionalized silver nanowires as hydrogen donors in type II photopolymerization enables us to fabricate PMMA/AgNW nanocomposites under mild conditions such as ambient temperature and solvent-free formulation. The morphology of nanocomposites is investigated by using scanning electron microscopy and compared by a solution mixing sample that prepared identical experimental condition. The distribution of AgNWs in the in-situ prepared nanocomposite is much homogenous than the solution mixing sample. The results from thermogravimetric analysis and differential scanning calorimetry clearly indicated that thermal behaviour of the nanocomposites is slightly improved than that of neat PMMA.
Keywords: Hydrogen Donor; Conductive Nanocomposites; Silver Nanowires; Free-Radical Polymerization; Photoinduced Electron-Transfer; Nanocomposites; In-Situ Synthesis; Transparent; Nanoparticles; Type II Photopolymerization; Graphene Oxide; Visible-Light; Epoxy Nanocomposites; Composites